Limiting equilibrium of a plane with a circular hole - Lozhkin, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The elastoplastic state of a compressible isotropic plane with a circular hole is studied by the method of a small parameter. An unknown boundary separating the domain of limiting equilibrium and the elastic domain is determined. We construct the complex Kolosov-Muskhelishvili functions that describe the elastic state of a plane and compare these with the solutions of Galin’s problem.